A Case of Spontaneous Transdiaphragmatic Intercostal Hernia with Contralateral Injury, and Review of the Literature. (23rd February 2017) - Chapman, Alexander A.; Duff, Steven B.
Abstract : This case report discusses the diagnosis and management of a 67-year-old male presenting with a spontaneous transdiaphragmatic intercostal hernia with contralateral intercostal hernia. The patient had a history of chronic obstructive pulmonary disease (COPD) exacerbations requiring multiple prolonged courses of steroids. The patient was ultimately diagnosed with computed tomography (CT) and underwent surgical repair via thoracotomy with primary repair of the diaphragmatic defect. The patient's postoperative course was uncomplicated. A review of the literature since the first similar case in 1977 recognizes the propensity of this injury to be found in patients with COPD and chronic steroid usage, as well as its diagnosis and management. The case reviewed is the second documented case of a concurrent abdominal wall herniation and the first one with a contralateral injury. It is important for clinicians to be aware of this pathology when evaluating patients with COPD and chronic steroid usage.